Gender-dependent association of a ÃÂ²2-adrenergic gene variant with obesity parameters in Malaysian Malays - Apalasamy, Y.D.; Ming, M.F.; Rampal, S.; Bulgiba, Awang; Mohamed, Z. (SAGE Publications, 2011)
Recent findings have shown that the rs1042714 (Gln27Glu) single-nucleotide polymorphism (SNP) on the Î²2-adrenoceptor gene may predispose to obesity. The findings from other studies carried on different populations, however, have been inconsistent. The authors investigated the association between the rs1042714 SNP with obesity-related parameters. DNA of 672 Malaysian Malays was analyzed using real-time polymerase chain reaction. Univariate and multivariate linear regression analyses revealed significant associations between rs1042714 and diastolic blood pressure in the pooled Malaysian Malay subjects under additive and recessive models. After gender stratification, however, a significant association was found between the rs1042714 and triglyceride and the rs1042714 and log-transformed high-density lipoprotein cholesterol levels in Malaysian Malay men. No significant association was found between the SNP and log-transformed body mass index. This polymorphism may have an important role in the development of obesity-related traits in Malaysian Malays. Gender is an effect modifier for the effect of the rs1042714 polymorphism on obesity-related traits in Malaysian Malays.